Highly Organized Ferrocene‐Functionalized Nanoporous Silica Films with an Extremely Fast Electron‐Transfer Rate for an Intrinsically Nonconducting Oxide‐Modified Electrode. Issue 11 (28th July 2015) - Audebert, Pierre; Vilà, Neus; Allain, Clémence; Maisonneuve, Franck; Walcarius, Alain; Hapiot, Philippe
Abstract: Modified electrodes from functionalized nanoporous xerogel coatings, prepared by using the electrochemically assisted self‐assembly (EASA) method, containing ferrocene moieties grafted onto vertically oriented pores perpendicular to an indium tin oxide (ITO) electrode, have been prepared and studied. The electrochemical behavior of these new materials exhibits the fastest charge transfer ever observed in oxide‐modified electrodes. The cyclic voltammetry curves allow us, however, to discriminate two types of ferrocene species inside the coatings and to determine the rate constants for the electron exchange between the ITO electrode and the coatings, with the help of simulations and an advanced software package. Abstract : Electrodes made EASA : Highly ordered nanoporous silica layers are obtained by using an adequately functionalized ferrocene–siloxane, resulting in the occurrence of extremely fast diffusion‐like hopping between the pendent ferrocene groups attached to the mesopore channels. In addition, these electrodes feature two different populations of active groups, which can be differentiated by the kinetics of electron exchange with the electrode.